Espaços públicos de lazer e saúde mental em Ribeirão Preto, SP - Duarte, Maria Raquel Barbosa (2023)
Could the city contribute to the promotion of mental health? Would the availability and the quality of public open spaces enable their use for therapeutic purposes? The research objective is to investigate how outdoor recreation spaces can be used in mental health care - based on deinstitutionalization, on restoring community ties, on independence and on the psychosocial inclusion of the person in mental distress. This study aimed to identify different practices in the process of psychosocial rehabilitation held in open spaces; to verify the pros and cons of public open spaces in Ribeirão Preto, SP, Brazil in fostering CAPS users’ autonomy, well-being, and coexistence. The research contributes to the discussions on urban quality focusing on people in psychological distress. To this end, the research method consisted in compiling a history of mental health care facilities in the city since the 1940s until the establishment of the current Psychosocial Care Network. The integration between urban and mental health policies was verified in legislation at the national and local levels. Subsequently, plans and projects aimed at promoting mental health were analyzed. Next, we carried out a systematic review of the literature on therapeutic activities developed in open spaces in the Brazilian context, and the spatial characteristics that favor them. Lastly, leisure spaces around the Psychosocial Care Centers in Ribeirão Preto were evaluated using quali-quantitative criteria. The six criteria are: availability of leisure spaces close to mental health services, accessibility by public transport, pedestrian accessibility, land use, vegetation shading and availability of urban furniture. Information on these criteria was obtained through document analysis and on-site data collection of leisure spaces attributes. Based on the established diagnosis, guidelines related to the spatial dimension of Mental Health were indicated. Eight out of the twenty-one public open spaces studied were considered adequate. The main inadequacies of these places are related to the lack of accessibility by public transport and the absence of adequate urban furniture.